Manganese peroxidase mRNA and enzyme activity levels during bioremediation of polycyclic aromatic hydrocarbon-contaminated soil with Phanerochaete chrysosporium. - Bogan, B W (1996)
mRNA extraction from soil and quantitation by competitive reverse transcription-PCR were combined to study the expression of three manganese peroxidase (MnP) genes during removal of polycyclic aromatic hydrocarbons from cultures of Phanerochaete chrysosporium grown in presterilized soil. Periods of high mnp transcript levels and extractable MnP enzyme activity were temporally correlated, although separated by a short (1- to 2-day) lag period. This time frame also coincided with maximal rates of fluorene oxidation and chrysene disappearance in soil cultures, supporting the hypothesis that high ionization potential polycyclic aromatic hydrocarbons are oxidized in soil via MnP-dependent mechanisms. The patterns of transcript abundance over time in soil-grown P. chrysosporium were similar for all three of the mnp mRNAs studied, indicating that transcription of this gene family may be coordinately regulated under these growth conditions.